Effects of static and dynamic stretching on joint position sense in artistic gymnasts - Amalia Drakou; Dimitris Chatzopoulos; Rodoula Gouliamperi; Georgios Lykesas; Sophia D. Papadopoulou; Styliani Douka (Central European Journal of Sport Sciences and Medicine)
This study aimed to examine the effects of static and dynamic stretching as part of warm up routines on shoulder and knee joint position sense in artistic gymnasts. A randomized crossover design was employed, involving twenty-six artistic gymnastics athletes (age = 8.94 ±1.11 yr.), who performed on three separate days the following protocols: (a) 3 min of jogging followed by dynamic stretching, (b) 3 min of jogging followed by static stretching, and (c) 3 min of jogging without stretching. After the 3 protocols the athletes performed the active angle reproduction test for shoulder and knee joint position sense. The repeated measures ANOVA revealed no significant differences between static and dynamic stretching concerning shoulder and knee joint position sense. Gymnasts devote much of their training to stretching routines, resulting in exceptional flexibility compared to other athletes. Thus, warm-up stretching may not significantly alter young gymnasts’ musculotendinous units, leaving their joint position sense unaffected. Moreover, the study sample consisted of young athletes, who have lower musculotendinous stiffness than adults, possibly making their joint position sense less affected by stretching due to their inherent lower stiffness. This study’s findings indicate that 30-second warm-up static stretching does not adversely affect shoulder and knee joint position sense in gymnasts.